Arbetsvillkor och algoritmer - En arbetsrättslig studie om förslaget till genomförande av plattformsdirektivets dubbla skyddsintressen i SOU 2026:3 - Syrtén,Ebba (2026)
This thesis examines the protection provided by the Platform Work Directive and whether the protection thereby prescribed can be considered sufficiently ensured through the proposed implementation set out in SOU 2026:3, Implementation of the Platform Work Directive. The thesis further examines whether the implementation of the Directive’s protective interests proposed by the inquiry is appropriate from a Swedish labour law perspective, in particular regarding the Swedish labour market model, the Swedish concept of employee status, the autonomy of the social partners and the rights relating to collective bargaining and negotiation. One consequence of the expanding digital labour market is the emergence of new business operations and business models. An increase in such activities in turn generates additional working opportunities. One example of this is digital labour platforms, which engage persons performing platform work. The fact that digital labour platforms create further working opportunities is not in itself problematic; however, issues arise when there is insufficient legislation protecting platform workers’ working conditions and personal data protection. These constitutes some of the protective interests which the Platform Work Directive seeks to safeguard. Pursuant to Article 288 TFEU, the Member States of the European Union are under an obligation to implement EU directives within their domestic legal systems. National legislation must conform with the directive, while existing national law must simultaneously be considered. The thesis applies a legal dogmatic method with elements of a legal policy analysis, together with an EU law methodology, to analyse how the inquiry in SOU 2026:3 has balanced these two competing interests through Sweden’s implementation of the Platform Work Directive. In the discussion concerning whether the inquiry has proposed an appropriate implementation of the Directive, the thesis concludes that the objectives pursued by the EU through the Platform Work Directive do not necessarily correspond with the structure of the Swedish labour market. Several of the concerns expressed in the Directive and its recitals, as well as in international legal literature, do not appear to be reflected either in the Swedish inquiry or in the consultation responses submitted by the social partners. Since the overall conclusion reached in the thesis is that SOU 2026:3 proposes an implementation capable of ensuring the protection afforded by the Platform Work Directive, the question that rises instead is whether the detailed nature of the Directive’s regulation is proportionate in relation to the internal legal systems of the Member States.
Keywords: Arbetsrätt; EU-rätt; Plattformsdirektivet; Plattformsarbete; Gig-ekonomi; SOU 2026:3; Labour Law; European Union Law; Platform Work Directive; Platform work